Utilization of sugarcane industry effluent for high value biomass and photosynthetic pigments production of Chlorella vulgaris (PSBDU06). (September 2019) - Jasmin Nivetha, B.; Bhakyalakshmi, S.V.; Dinesh Kumar, S.; Santhanam, P.; Vijayalakshmi, D.; Divya, M.; Krishnaveni, N.
Abstract: A huge amount of pollutant free water required for sugarcane processing industry to obtain sugarcane byproducts. It is estimated that approximately 1–2 m 3 of water being used to practice 1 ton of sugarcane and this process will generate 1 m 3 as polluted effluent. This work has been dealt with treating sugarcane industry (SCI) effluent by bio cultivation of Chlorella vulgaris (PSBDU06). The cultivation of C. vulgaris in SCI effluent was also evaluated by dilution of effluent and adding external nutrient sources. The addition of KNO3 and 10% WW dilution resulted higher nutrients consumption (PO 3− 4 -93.67 ± 4.69%, NO −3 -66.33 ± 3.32%, NO −2 -64.21 ± 3.21%, SiO3 2— 83.49 ± 4.17%), than others. The higher biomass (6.85 ± 0.34 g L −1 ) and photosynthetic pigments (2.87 ± 0.14 μg L −1 ) production could be achieved at a 10% WW and potassium nitrate combination. The combined bio cultivation of C. vulgaris with external additional nutrients sources with lowest dilution of SCI effluent shows excellent removal of nutrients and high value algal products achieved. Highlights: Cultivation of C. vulgaris in SCI effluent resulted 93.67 ± 4.69% of PO 3− 4 removal Lowest dilution of SCI effluent with external nutrients shows significant results. 6.85 ± 0.34 g L −1 of biomass production suggesting SCI effluent as alternative medium